ANALYSIS OF PHYTOCHEMICAL SUBSTANCE AND THE EFFECT OF CANG SALAK TEA (CST) DIET TO LIPID PROFILE ON HYPERLIPIDEMIC RAT - Karta, I Wayan; Burhannuddin, Burhannuddin; Kartawidjajaputra, Felicia (JST (Jurnal Sains dan Teknologi), 2021)
The bark of Sibetan snakefruit (Salacca zalacca) and sappan wood (Caesalpinia sappan L.) are combined into the product of Cang Salak Tea (CST). This tea is expected to be useful for diseases associated with dyslipidemia. The purpose of this study was to examine the secondary metabolites in CST and to determine the effect of CST treatment on the lipid profile of total cholesterol (TC), triglyceride (TG), HDL, and LDL level. Wistar rats were divided into three groups: control group (K), hyperlipidemic rats group given CST (P1), and hyperlipidemic rat group without CST treatment. Group P1 was given CST as much as 1.2 mL per day for 4 weeks. CST contains alkaloid, flavanoid, tannin, phenol, and saponine. Flavonoid level about 81.026 ppm; tannin 525.706 ppm, IC50 177.689 ppm, and phenol 622.7844 ppm. There were significant differences in the lipid profile of K and P1 with P2. CST treatment to hyperlipidemic rats can reduce total cholesterol and normalize level of TG, HDL, and LDL. The active substance in CST has role in lipid metabolism, so it can improve the lipid profile of hyperlipidemic rats.